Tactile Sensory Dysfunction in Children with ADHD - Ahmad Ghanizadeh (Behavioural Neurology)
Objectives: While a group of children with ADHD may have normal behavioral responses to sensory stimuli, another group may be hyperreactive. The aim of this survey was studying association of tactile sensory responsivity with co-morbidity of oppositional defiant disorder (ODD) symptoms, subtypes of ADHD, and gender in children with ADHD.